Knowledge Integration within the Bachelor of Arts Curriculum in Home Economics, Faculty of Education, for Academic Services to the Community and Society: A Case Study of Thepleela Community, Wang Thonglang District, Bangkok - Thongyaem, Phopnapahat; Purahong , Warong; Punbua, Nathasar; Sawangsook, Poochit; Hongkham, Thosang; Rattanasiri, Muanpare; Masantiah, Chuthaphon (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: This study examines the knowledge integration within the Bachelor of Arts curriculum in Home Economics offered by the Faculty of Education, focusing on the impact on academic services to the community and society. The research was conducted in the Thepleela community in Wang Thonglang district, Bangkok. The researcher carried out activities to promote good health and well-being (SDGs 3), which are aligned with the 17 Sustainable Development Goals (SDGs). One important initiative was the “Clean Food & Good Health” program, which demonstrated the preparation of the “Om-Yim Sandwich”. This program incorporated knowledge integration from the Bachelor of Arts curriculum in Home Economics. The research objectives were: (1) to explore the outcomes of knowledge integration within the Bachelor of Arts curriculum in Home Economics on the recipients of academic services in the community and society, and (2) to explore the results of the knowledge integration within the Bachelor of Arts curriculum in Home Economics on the providers of these academic services. Methodology: In the study, data were collected from 50 community members of Thepleela community using a questionnaire with a 5-point Likert scale with 20 items and analyzed using descriptive statistics, including mean and standard deviation. In examining the outcomes of knowledge integration on service providers, data were collected through semi-structured interviews with three students and six faculty members responsible for the course. The qualitative data were analyzed using content analysis and validated through triangulation. Results: The research results showed that (1) Overall satisfaction with the knowledge integration within the Bachelor of Arts curriculum in Home Economics among community and social academic service recipients was very high. Specifically, (1) satisfaction with the operational approach was highest and (2) satisfaction with outcomes related to product quality, pricing, and promotion was also highest. (2) The outcomes on academic service providers in terms of instruction showed that six faculty members experienced comprehensive outcomes in three dimensions: cognitive, affective, and psychomotor domains. The three students who participated in the activities also achieved learning outcomes that encompassed these three domains. Conclusion: In summary, knowledge integration in the Bachelor of Arts curriculum in Home Economics results in positive outcomes for both service recipients, who are community members in Thepleela, and service providers, including faculty members and students in the program.